Baudrillard’s postmodernist perspective on aggression and violence expression in online media comment columns - Yanuar, Fit; Widaningsih, Titi; Oktavianti, Roswita; Ekayanthi, Daesy (Universitas Bunda Mulia, 2025)
This study attempts to bridge the thoughts of a postmodernist thinker, Jean Baudrillard, with the contemporary phenomenon of aggression and violence exhibited by online media audiences, particularly through the comment sections. These online audiences actively engage in comment sections by expressing aggressive and violent messages. Jean Baudrillard’s postmodernist perspective argues that consumers in the advanced information technology era can be deceived by systems created by capitalist entities. In alignment with this theme, the author establishes a correlation between media entrepreneurs' manipulation of online media consumers—through the engineered structure of comment sections—and the emergence of aggressive and violent communication behavior among online commenters. Referring to Baudrillard's notion, the comment section activity in online media can be regarded as a rather ecstatic form of communication that intoxicates its users and prompting continuous engagement, including the proliferation of aggressive and violent messages. This study employs the critical discourse analysis method introduced by Teun A. van Dijk, known as the Social Cognition Model. This model integrates three fundamental components of analysis: text, social cognition, and social context. It posits that any text appearing in the media is intrinsically linked to societal cognition and the underlying social context. From a societal perspective, aggressive and violent communication messages in online comment sections do not contribute positively or provide solutions to societal problems. Practically, this study seeks to propose viable solutions to these issues.